Foundational Research Gaps and Future Directions for Digital Twins - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Across multiple domains of science, engineering, and medicine, excitement is growing about the potential of digital twins to transform scientific research, industrial practices, and many aspects of daily life. A digital twin couples computational models with a physical counterpart to create a system that is dynamically updated through bidirectional data flows as conditions change. Going beyond traditional simulation and modeling, digital twins could enable improved medical decision-making at the individual patient level, predictions of future weather and climate conditions over longer timescales, and safer, more efficient engineering processes. However, many challenges remain before these applications can be realized. This report identifies the foundational research and resources needed to support the development of digital twin technologies. The report presents critical future research priorities and an interdisciplinary research agenda for the field, including how federal agencies and researchers across domains can best collaborate.
Keywords: Computers and Information Technology; Math, Chemistry, and Physics

Frontiers in Massive Data Analysis - National Research Council (The National Academies Press, 2013)
Data mining of massive data sets is transforming the way we think about crisis response, marketing, entertainment, cybersecurity and national intelligence. Collections of documents, images, videos, and networks are being thought of not merely as bit strings to be stored, indexed, and retrieved, but as potential sources of discovery and knowledge, requiring sophisticated analysis techniques that go far beyond classical indexing and keyword counting, aiming to find relational and semantic interpretations of the phenomena underlying the data. Frontiers in Massive Data Analysis examines the frontier of analyzing massive amounts of data, whether in a static database or streaming through a system. Data at that scale--terabytes and petabytes--is increasingly common in science (e.g., particle physics, remote sensing, genomics), Internet commerce, business analytics, national security, communications, and elsewhere. The tools that work to infer knowledge from data at smaller scales do not necessarily work, or work well, at such massive scale. New tools, skills, and approaches are necessary, and this report identifies many of them, plus promising research directions to explore. Frontiers in Massive Data Analysis discusses pitfalls in trying to infer knowledge from massive data, and it characterizes seven major classes of computation that are common in the analysis of massive data. Overall, this report illustrates the cross-disciplinary knowledge--from computer science, statistics, machine learning, and application disciplines--that must be brought to bear to make useful inferences from massive data.
Keywords: Math, Chemistry, and Physics; Surveys and Statistics

Massive Data Sets: Proceedings of a Workshop - National Research Council (The National Academies Press, 1996)
Keywords: Math, Chemistry, and Physics; Computers and Information Technology; Surveys and Statistics

Statistical Analysis of Massive Data Streams: Proceedings of a Workshop - National Research Council (The National Academies Press, 2004)
Massive data streams, large quantities of data that arrive continuously, are becoming increasingly commonplace in many areas of science and technology. Consequently development of analytical methods for such streams is of growing importance. To address this issue, the National Security Agency asked the NRC to hold a workshop to explore methods for analysis of streams of data so as to stimulate progress in the field. This report presents the results of that workshop. It provides presentations that focused on five different research areas where massive data streams are present: atmospheric and meteorological data; high-energy physics; integrated data systems; network traffic; and mining commercial data streams. The goals of the report are to improve communication among researchers in the field and to increase relevant statistical science activity.
Keywords: Computers and Information Technology; Math, Chemistry, and Physics; Surveys and Statistics

Training Students to Extract Value from Big Data: Summary of a Workshop - National Research Council (The National Academies Press, 2015)
As the availability of high-throughput data-collection technologies, such as information-sensing mobile devices, remote sensing, internet log records, and wireless sensor networks has grown, science, engineering, and business have rapidly transitioned from striving to develop information from scant data to a situation in which the challenge is now that the amount of information exceeds a human's ability to examine, let alone absorb, it. Data sets are increasingly complex, and this potentially increases the problems associated with such concerns as missing information and other quality concerns, data heterogeneity, and differing data formats. The nation's ability to make use of data depends heavily on the availability of a workforce that is properly trained and ready to tackle high-need areas. Training students to be capable in exploiting big data requires experience with statistical analysis, machine learning, and computational infrastructure that permits the real problems associated with massive data to be revealed and, ultimately, addressed. Analysis of big data requires cross-disciplinary skills, including the ability to make modeling decisions while balancing trade-offs between optimization and approximation, all while being attentive to useful metrics and system robustness. To develop those skills in students, it is important to identify whom to teach, that is, the educational background, experience, and characteristics of a prospective data-science student; what to teach, that is, the technical and practical content that should be taught to the student; and how to teach, that is, the structure and organization of a data-science program. Training Students to Extract Value from Big Data summarizes a workshop convened in April 2014 by the National Research Council's Committee on Applied and Theoretical Statistics to explore how best to train students to use big data. The workshop explored the need for training and curricula and coursework that should be included. One impetus for the workshop was the current fragmented view of what is meant by analysis of big data, data analytics, or data science. New graduate programs are introduced regularly, and they have their own notions of what is meant by those terms and, most important, of what students need to know to be proficient in data-intensive work. This report provides a variety of perspectives about those elements and about their integration into courses and curricula.
Keywords: Math, Chemistry, and Physics; Education; Surveys and Statistics

Big Data and Analytics for Infectious Disease Research, Operations, and Policy: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
With the amount of data in the world exploding, big data could generate significant value in the field of infectious disease. The increased use of social media provides an opportunity to improve public health surveillance systems and to develop predictive models. Advances in machine learning and crowdsourcing may also offer the possibility to gather information about disease dynamics, such as contact patterns and the impact of the social environment. New, rapid, point-of-care diagnostics may make it possible to capture not only diagnostic information but also other potentially epidemiologically relevant information in real time. With a wide range of data available for analysis, decision-making and policy-making processes could be improved.
Keywords: Health and Medicine; Math, Chemistry, and Physics; Surveys and Statistics

Refining the Concept of Scientific Inference When Working with Big Data: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The concept of utilizing big data to enable scientific discovery has generated tremendous excitement and investment from both private and public sectors over the past decade, and expectations continue to grow. Using big data analytics to identify complex patterns hidden inside volumes of data that have never been combined could accelerate the rate of scientific discovery and lead to the development of beneficial technologies and products. However, producing actionable scientific knowledge from such large, complex data sets requires statistical models that produce reliable inferences (NRC, 2013). Without careful consideration of the suitability of both available data and the statistical models applied, analysis of big data may result in misleading correlations and false discoveries, which can potentially undermine confidence in scientific research if the results are not reproducible. In June 2016 the National Academies of Sciences, Engineering, and Medicine convened a workshop to examine critical challenges and opportunities in performing scientific inference reliably when working with big data. Participants explored new methodologic developments that hold significant promise and potential research program areas for the future. This publication summarizes the presentations and discussions from the workshop.
Keywords: Math, Chemistry, and Physics; Engineering and Technology; Policy for Science and Technology; Surveys and Statistics

Chemistry and Engineering of Shale Gas and Tight Oil Resource Development: Workshop in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
Oil and gas exploration in the United States has expanded with the increased use of horizontal, or directional, drilling to facilitate the recovery of shale gas and tight oil resources. The U.S. Environmental Protection Agency estimates that 25,000 to 30,000 new hydraulic fracturing wells were drilled each year between 2011 and 2014, and the impact of those wells and the use of hydraulic fracturing has been a topic of public and policy discussion in recent years. Though chemistry and chemical engineering are used extensively in the hydraulic fracturing process, their roles are not well understood outside of the oil and gas industries. In a workshop held May 18-19, 2015 in Washington, DC by the Chemical Sciences Roundtable, practitioners and experts in these fields came together to discuss shale gas and tight oil resource development. This report summarizes the presentations and discussions from the workshop.
Keywords: Math, Chemistry, and Physics; Engineering and Technology; Energy and Energy Conservation

Symposium on Microseisms: Held at Arden House, Harriman, N.Y. 4-6 September 1952, Sponsored by the Office of Naval Research, and the Geophysical Research Directorate of the U.S. Air Force. - National Research Council (The National Academies Press, 1953)
Keywords: Math, Chemistry, and Physics

A Research Agenda for Transforming Separation Science - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Separation science plays a critical role in maintaining our standard of living and quality of life. Many industrial processes and general necessities such as chemicals, medicines, clean water, safe food, and energy sources rely on chemical separations. However, the process of chemical separations is often overlooked during product development and this has led to inefficiency, unnecessary waste, and lack of consensus among chemists and engineers. A reevaluation of system design, establishment of standards, and an increased focus on the advancement of separation science are imperative in supporting increased efficiency, continued U.S. manufacturing competitiveness, and public welfare.
Keywords: Math, Chemistry, and Physics

Regional Dialogues on the Changing Environment for the Physical and Mathematical Sciences: Report of Two Conferences (The National Academies Press, 1995)

Radiochemistry of Mercury - National Research Council (The National Academies Press, 1970)

The Changing Landscape of Hydrocarbon Feedstocks for Chemical Production: Implications for Catalysis: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
A decade ago, the U.S. chemical industry was in decline. Of the more than 40 chemical manufacturing plants being built worldwide in the mid-2000s with more than $1 billion in capitalization, none were under construction in the United States. Today, as a result of abundant domestic supplies of affordable natural gas and natural gas liquids resulting from the dramatic rise in shale gas production, the U.S. chemical industry has gone from the world's highest-cost producer in 2005 to among the lowest-cost producers today.
Keywords: Math, Chemistry, and Physics

Opportunities in Chemistry - National Research Council (The National Academies Press, 1985)
Opportunities in Chemistry is based on the contributions of hundreds of American chemists in academia and industry and should be taken as the best available consensus of the chemical community regarding its intellectual frontiers and the economic opportunities that lie beyond them," says Science. This volume addresses the direction in which today's chemical research is heading, including recent developments, technological applications, and the ways advances in chemistry can be used to improve the human condition. In addition, the book examines economic and political implications of chemical research and lists resources for basic research and education in the chemical sciences.
Keywords: Math, Chemistry, and Physics

Eighteenth Symposium on Naval Hydrodynamics - National Research Council (The National Academies Press, 1991)
This volume contains technical papers and discussions covering ship motions, ship hydrodynamics, experimental techniques, free-surface aspects, wave/wake dynamics, propeller/hull/appendage interactions, and viscous effects.
Keywords: Math, Chemistry, and Physics

Frontiers in Chemical Engineering: Research Needs and Opportunities - National Research Council (The National Academies Press, 1988)
In the next 10 to 15 years, chemical engineers have the potential to affect every aspect of American life and promote the scientific and industrial leadership of the United States. Frontiers in Chemical Engineering explores the opportunities available and gives a blueprint for turning a multitude of promising visions into realities. It also examines the likely changes in how chemical engineers will be educated and take their place in the profession, and presents new research opportunities.
Keywords: Math, Chemistry, and Physics

Catalysis Looks to the Future - National Research Council (The National Academies Press, 1992)
The impact of catalysis on the nation's economy is evidenced by the fact that catalytic technologies generate U.S. sales in excess of $400 billion per year and a net positive balance of trade of $16 billion annually. This book outlines recent accomplishments in the science and technology of catalysis and summarizes important likely challenges and opportunities on the near horizon. It also presents recommendations for investment of financial and human resources by industry, academe, national laboratories, and relevant federal agencies if the nation is to maintain continuing leadership in this field—one that is critical to the chemical and petroleum processing industries, essential for energy-efficient means for environmental protection, and vital for the production of a broad range of pharmaceuticals.
Keywords: Math, Chemistry, and Physics

Why Indoor Chemistry Matters - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
People spend the vast majority of their time inside their homes and other indoor environments where they are exposed to a wide range of chemicals from building materials, furnishings, occupants, cooking, consumer products, and other sources. Despite research to date, very little is known about how exposures to indoor chemicals across complex chemical phases and pathways affect human health. The COVID-19 pandemic has only increased public awareness of indoor environments and shed light on the many outstanding questions about how best to manage chemicals indoors. This report identifies gaps in current research and understanding of indoor chemistry and new approaches that can be applied to measure, manage, and limit chemical exposures. Why Indoor Chemistry Matters calls for further research about the chemical transformations that can occur indoors, pathways and timing of indoor chemical exposure, and the cumulative and long-term impacts of exposure on human health. Research priorities should consider factors that contribute to measurable environmental health disparities that affect vulnerable populations, such as the age, location, and condition of buildings that can alter exposures to indoor chemicals.
Keywords: Math, Chemistry, and Physics; Environment and Environmental Studies

Research Teams and Partnerships: Trends in the Chemical Sciences, Report of a Workshop - National Research Council (The National Academies Press, 1999)
The third workshop of the Chemical Sciences Roundtable, Research Teams and Partnerships was held in Irvine, California, on May 2-3, 1999. The presentations and discussions at the workshop considered the current status of research partnerships in the chemical sciences and methods to improve the ability to form and maximize such collaborations. This volume presents the results of that workshop.
Keywords: Math, Chemistry, and Physics; Surveys and Statistics

The Importance of Chemical Research to the U.S. Economy - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Chemistry plays a pivotal role in the strength of the U.S. economy and the advancement of humankind. Chemists' achievements include life-saving pharmaceuticals, advanced energy solutions, improved agricultural productivity, and novel materials used in products from clothing to electronic devices. The many sectors reliant on the U.S. chemical economy account for about 25% of the U.S. GDP and support 4.1 million U.S. jobs. However, a new and evolving chemistry landscape requires changes with regard to funding, training, and a focus on integrating sustainability into manufacturing, product usage, and product disposal. This report identifies strategies and options for research investments that will support U.S. leadership while considering environmental sustainability and developing a diverse chemical economy workforce with equitable opportunities for all chemistry talent. The report recommends that funding agencies and philanthropic organizations who support the chemical sciences fund as large a breadth of fundamental research projects as possible. Chemical industry and their partners at universities, scientific research institutions, and national laboratories should align the objectives of fundamental research to directly assist with new practices toward environmental stewardship, sustainability, and clean energy. Additionally, the report recommends that funding agencies make substantial investment toward education research to enable innovative ways of teaching about emerging concepts, tools and technologies.
Keywords: Math, Chemistry, and Physics; Industry and Labor